Effects Of Prompts And Recasts On Second Language Writing In English As a Foreign Language A2 Learners Of An Ecuadorian Public University - Espol (2018)
The purpose of this study was to compare the effects of prompts or recasts on the level of writing of english as a foreign language a2 learners of an ecuadorian public university. 23 ecuadorian efl students participated in this study. they were assigned to the recast and prompt groups through a convenience sampling strategy. findings suggest that there was not a significant difference between the effect of prompts or recasts in terms of grammar, sentence formation, spelling/punctuation and vocabulary. however, the overall level of writing within each experimental group did slightly improve after the intervention, but with no significant statistical difference. this provides evidence that supports the overall efficacy of feedback on students’ level of writing. however, such findings are not at all conclusive.keywords: compare, effects, prompts, recats, level of writing, significant, difference